2016
DOI: 10.4244/eijy15m05_07
|View full text |Cite
|
Sign up to set email alerts
|

First-in-man evaluation of the novel balloon delivery system STENTYS Xposition S for the self-apposing coronary artery stent: impact on longitudinal geographic miss during stenting

Abstract: This first-in-man study demonstrated that the use of the novel STENTYS Xposition S balloon delivery system is feasible with a high technical success rate without longitudinal geographical miss. Stent strut malapposition rate directly after STENTYS placement was low and improved further after post-dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Of note, in the present study we included both the first generation of SES with the traditional Stentys release system and the more recent balloon‐delivered Xposition Stentys. As previously reported, these peculiar release systems did not appear to represent a substantial limitation to the use of these devices and they did not appear to relate to a higher rate of early definite ST and early adverse events in the SES group.…”
Section: Discussionsupporting
confidence: 68%
“…Of note, in the present study we included both the first generation of SES with the traditional Stentys release system and the more recent balloon‐delivered Xposition Stentys. As previously reported, these peculiar release systems did not appear to represent a substantial limitation to the use of these devices and they did not appear to relate to a higher rate of early definite ST and early adverse events in the SES group.…”
Section: Discussionsupporting
confidence: 68%
“…The latest Stentys Xposition S with balloon delivery system has radioopaque stent end markers to enhance precise placement of the stent. We concur with the SETUP study that postdilatation is still necessary as we also discovered significant immediate stent strut malapposition post stent deployment [4]. Despite repeated OCT guided balloon postdilatations, residual minor strut malapposition remained and hopefully, the nitinol based stent with self-expanding nature would conform to the vessel wall over time.…”
supporting
confidence: 85%
“…SETUP study authors suggested that Stentys Xposition S would be suitable and appropriate for cases with potential risk of stent malpositioning and mis-sizing [4]. Our case complicated with the LM-LAD anatomy, bifurcation and ectasia vessel factors with large and unpredictable diameter differences, rendering it highly susceptible to stent malpositioning and mis-sizing risks.…”
mentioning
confidence: 93%
“…Also, optimal positioning was challenging with the older generation STENTYS stent because of shortening of the stent at deployment due to retracting an outer sheath which releases the stent from the distal edge. A novel balloon delivery system for the STENTYS SES, (the STENTYS Xposition), was therefore developed to improve accurate stent positioning[ 21 ].…”
Section: Limitations Of the Studymentioning
confidence: 99%